2017
DOI: 10.1038/ncomms15763
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz saturable absorbers from liquid phase exfoliation of graphite

Abstract: Saturable absorbers (SA) operating at terahertz (THz) frequencies can open new frontiers in the development of passively mode-locked THz micro-sources. Here we report the fabrication of THz SAs by transfer coating and inkjet printing single and few-layer graphene films prepared by liquid phase exfoliation of graphite. Open-aperture z-scan measurements with a 3.5 THz quantum cascade laser show a transparency modulation ∼80%, almost one order of magnitude larger than that reported to date at THz frequencies. Fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
124
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(127 citation statements)
references
References 71 publications
3
124
0
Order By: Relevance
“…Following this, Bianco et al [118] experimentally demonstrated a graphene-based saturable absorber that exhibited a ≈10% increase in transmittance upon saturation. Recently, an improvement in graphene's SA was demonstrated by Bianchi et al [119] While several semiconductors such as GaAs, GaP, www.advopticalmat. de and Ge have been shown to possess saturable absorption in terahertz wavelengths, [120] utilizing graphene provides the added benefit of intracavity integration in subwavelength cavities while incurring minimal losses.…”
Section: Terahertz Saturable Absorbersmentioning
confidence: 99%
“…Following this, Bianco et al [118] experimentally demonstrated a graphene-based saturable absorber that exhibited a ≈10% increase in transmittance upon saturation. Recently, an improvement in graphene's SA was demonstrated by Bianchi et al [119] While several semiconductors such as GaAs, GaP, www.advopticalmat. de and Ge have been shown to possess saturable absorption in terahertz wavelengths, [120] utilizing graphene provides the added benefit of intracavity integration in subwavelength cavities while incurring minimal losses.…”
Section: Terahertz Saturable Absorbersmentioning
confidence: 99%
“…We recently demonstrated THz saturable absorbers by transfer coating and ink-jet printing 50 layer (randomly distributed) graphene films prepared by liquid phase exfoliation of graphite [39]. Through the combination of open-aperture z-scan experiments and Fourier transform infrared (FTIR) spectroscopy, we demonstrate 80% transparency modulation at 3.4 THz [39].…”
Section: Multilayer Graphene-based Saturable Absorbers At Thz Frequenmentioning
confidence: 99%
“…Here, we report on the first evidence of THz saturable absorption in multilayer graphene films, grown via CVD on Nickel. The as-grown multilayer graphene films was transferred onto an intrinsic silicon substrate, and tested by means of an open aperture z-scan transmission experiment following the same experimental procedure described in [39].…”
Section: Multilayer Graphene-based Saturable Absorbers At Thz Frequenmentioning
confidence: 99%
See 2 more Smart Citations